Rule-based Named Entity Recognition (NER) to Determine Time Expression for Balinese Text Document - Sinta Wahyuni, Ni Made; Sanjaya ER, Ngurah Agus (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 9 No 4 (2021): JELIKU Volume 9 No 4, Mei 2021, 2021)
Named Entity Recognition (NER) is a process to identify words or phrases as a named entity, such as a person, location, time expression, or organization. In this research, we are interested in developing a NER which able to identify the time expression entity in Balinese text documents. The time expression entity becomes an important component in the text because it is usually followed by important facts and information. NER was built using a rules-based approach. The rules are built based on direct observation of documents and pay attention to the morphological and contextual structures. Based on the experiments conducted, the average results of the precision, recall, and f-measure values were 0.85, 0.87, and 0.85.